Sosialisasi dan Pelatihan Pengolahan Sampah Organik di Lingkungan Organisasi Muhammadiyah Palangka Raya: Socialization and Training on Organic Waste Procesing in the Environment Organization Muhammadiyah of Palangka Raya - Rosawanti, Pienyani; Hakim, Muh. Supwatul; Azhari, Muh.; Norhalidah, Norhalidah; Pratama, Tegar (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Environmental problems, one of which is caused by human activities and in the form of waste, require special attention in managing, for example, organic solid waste. Organic waste problems are also among the environmental problems, for example in the city of Palangka Raya, which is affected by increasing population growth. Data from the Ministry of Environment and Forestry of the Republic of Indonesia shows that the amount of organic waste produced daily is 0.7 kg/person and 60% of its composition is organic waste. The method of implementing charitable activities is through socialization and demonstration, as well as the application of products to cultivated plants. The phases of the activities carried out include the preparation phase, the biomass crushing phase, the fermentation phase, the product harvesting phase, and the product application phase. The products of the service activities are solid organic fertilizer (compost) and liquid organic fertilizer (POC), i.e. the water produced during the decomposition process. The compost products are characterized by the fact that they are not sharp, brown, and moist. Hopefully, the charitable activities carried out can be easily applied by communities and organizations that need knowledge and implementation of charitable activities related to organic waste processing to alleviate environmental problems, such as the Muhammadiyah Organization of Palangka Raya City.